Supervising Acting Regional Heads: A Linkage of Central Government and Regional Legislative Council Supervision Function - Nasution, Ali Imran; Nahuddin, Yusuf Eko; Thohari, Ahmad Ahsin (Jurnal Cakrawala Hukum, 2024)
Simultaneous general elections will be held on November 27, 2024, to elect Regional Heads who officially end in 2022 and 2023 and have not participated in the first-period simultaneous election in 2020. The government directly appoints Acting Regional Heads to fill the office temporarily, as regulated in Article 201 paragraph (9) of Law No. 10/2016. This research analyzes the supervision system for Acting Regional Heads, which involves the role of the Central Government and Regional Legislative Council (DPRD). The result shows that the Minister of Home Affairs comprehensively evaluated Acting Regional Heads’ performance without involving the DPRD’s supervisory function. However, the Acting Regional Head is as authoritative as the Regional Head, as stated in Article 15, paragraph (1) of Minister of Home Affairs Regulation No. 4/2023 (Permendagri No. 4/2023). This research suggests reconstructing Permendagri No. 4/2023 to enhance DPRD’s authority to oversee Acting Regional Heads’ performance as an additional report used by the Minister of Home Affairs to evaluate Acting Regional Heads.